(untitled) (American Journal of Islam and Society, 2001)
Between Memory and Desire is a joy to read, since it does justice to many misunderstood subjects about Islam and the Middle East. Humphreys’ genuine effort to be objective saves him from dismissing the reality of the phenomenon he is observing with his subjective redefinition of it. Being objective need not involve giving up one’s set of values: it is neither desired nor possible not to have any values. Rather, objectivity is frankly to admit that we do have values through which we respond to what we observe. Because the author does this, he quite successfully compares and contrasts his own point of reference, i.e. contemporary American values, with Islamic values. Humphreys’ discussion not only will help the outsiders understand Islam and Middle Eastern phenomenon better, but also will enable the "insiders" to view how things look from outside and do self-criticism. In the first chapter, Hard Realities: Population Overgrowth and Economic Stagnation, the author considers the difficult economic situation of the Middle East. Humphreys notes that powerful market forces of the first world have negative impact on the Middle Eastern economy, an effect persisting from colonial times. This point could have been emphasized more, for the impact of the global capitalist economy on the ...